Novel I-doped Bi12O17Cl2 photocatalysts with enhanced photocatalytic activity for contaminants removal. (April 2019) - Guo, Minna; He, Heng; Cao, Jing; Lin, Haili; Chen, Shifu
Graphical abstract: Highlights: I-doped Bi12 O17 Cl2 was synthesized by a facile chemical precipitation method. I-doped Bi12 O17 Cl2 exhibited excellent photocatalytic activity. Impurity level was generated above the valence band of Bi12 O17 Cl2 . I − ions improved the separation efficiency of photoinduced charges. Abstract: Novel I-doped Bi12 O17 Cl2 photocatalysts have been synthesized using a facile chemical precipitation method and characterized by XRD, XPS, SEM, BET and UV–vis DRS etc. The corresponding results indicate that I − ions enter into the crystal lattices of Bi12 O17 Cl2 and replace partial Cl − ions. In addition, the doped I − ions form an impurity level over valence band and extend the visible light absorption ranges of Bi12 O17 Cl2 . I-doped Bi12 O17 Cl2 exhibits much superior visible-light (λ > 420 nm) photocatalytic activity to that of the pure Bi12 O17 Cl2 in the methyl orange (MO) and phenol degradation, because a little amount of I − ions can boost the photocharges separation efficiency, which is ensured by photoluminescence spectra, transient photocurrent responses and electrochemical impedance spectra. It is expected that this work opens a new potential pathway to improve the photocatalytic activity of non-stoichiometric ratios bismuth oxyhalide via ions doping strategy.